Synthesis, Characterization and Theoretical Study of Some Mixed-ligand Complexes of 2-Quinoline Carboxylic Acid and 4,4⁄ -dimethyl,2,2⁄-Bipyridyl with Some Transition Metal Ions - Alias, Mahasin; Ismael, Sahar; Mousa, Souad Abd (Al-Nahrain Journal of Science, 2018)
New mixed ligand complexes have been prepared by the reaction of Quinoline- 2-Carboxylic Acid (HL1) and 4,4⁄ -dimethyl,2,2⁄ -Bipyridyl (L2) with Co(II),Ni(II) u(II), Zn(II), Pd(II) and Au(III) ions. The newly prepared complexes were isolated and characterized by (FT-IR) and (UVVis) spectroscopy, elemental analysis, flame tomic absorption technique, thermo gravimetric analysis, in addition to magnetic susceptibility and conductivity measurements. A theoretical treatment of these ligands and prepared complexes in gas phase were studied using Hyper chem.8 program, moreover, ligands in gas phase also have been studied using Gaussian program (GaussView Currently Available Versions (5.0.9) along with Gaussian 09 which is the latest in the Gaussian series of programs).